(untitled) (Research, Society and Development, 2020)
How has the construction of guidelines and curricular architectures been given admittingthe relation between education and work? From this point of view, this study is based onthe reading of the field of critical curriculum theory, on the history of professional andtechnological education in Brazil and on the problematic approach to the relationship betweenschooling and professionalization. In the light of these studies, the objective was to analyze institutional publications related to curricular organization in the context of the technicalcourses offered by a public institution of professional and technological education in the State of São Paulo.